Taxonomy and phylogeny of brown-rot corticioid fungi in China: Coniophora beijingensis and Veluticeps subfasciculata spp. nov. - Li, Yue; He, Shuang-Hui (Frontiers in Microbiology, 2023)
Brown-rot fungi account for a small portion of the wood-decaying fungi. There are a few corticioid genera causing brown rot of wood, and their species diversity are still under investigated and studied, especially in subtropical and tropical areas. Two new brown-rot corticioid fungi, Coniophora beijingensis and Veluticeps subfasciculata were found during the investigation of corticioid fungi in China. Phylogenetic analyses of the two genera were carried out separately based on ITS-28S sequence data. Coniophora beijingensis was collected from Beijing, north China, from different kind of angiosperm and gymnosperm trees, and is characterized by possessing a monomitic hyphal system with colorless hyphae and relatively small pale yellow basidiospores 7–8.6 × 4.5–6 µm. Veluticeps subfasciculata was collected from Guizhou and Sichuan Provinces, southwestern China, on Cupressus and is characterized by the resupinate to effused-reflexed basidiomes with a colliculose hymenophore, nodose-septate generative hyphae, fasciculate skeletocystidia and subcylindrical to subfusiform basidiospores 8–11 × 2.5–3.5 µm. Descriptions and illustrations are provided for the two new species, and identification keys to Coniophora and Veluticeps species in China are given. Coniophora fusispora is reported in China for the first time.